The antibody‐based delivery of interleukin‐12 to solid tumors boosts NK and CD8+ T cell activity and synergizes with immune checkpoint inhibitors. Issue 9 (28th August 2019) - Puca, Emanuele; Probst, Philipp; Stringhini, Marco; Murer, Patrizia; Pellegrini, Giovanni; Cazzamalli, Samuele; Hutmacher, Cornelia; Gouyou, Baptiste; Wulhfard, Sarah; Matasci, Mattia; Villa, Alessandra; Neri, Dario
Abstract : We describe the cloning and characterization of a novel fusion protein (termed L19‐mIL12), consisting of murine interleukin‐12 in single‐chain format, sequentially fused to the L19 antibody in tandem diabody format. The fusion protein bound avidly to the cognate antigen (the alternatively spliced EDB domain of fibronectin), retained the activity of the parental cytokine and was able to selectively localize to murine tumors in vivo, as shown by quantitative biodistribution analysis. L19‐mIL12 exhibited a potent antitumor activity in immunocompetent mice bearing CT26 carcinomas and WEHI‐164 sarcomas, which could be boosted by combination with checkpoint blockade, leading to durable cancer eradication. L19‐mIL12 also inhibited tumor growth in mice with Lewis lung carcinoma (LLC), but in this case, cancer cures could not be obtained, both in monotherapy and in combination. A microscopic analysis and a depletion experiment of tumor‐infiltrating leukocytes illustrated the contribution of NK cells and CD8 + T cells for the anticancer activity observed in both tumor models. Upon L19‐mIL12 treatment, the density of regulatory T cells (Tregs) was strongly increased in LLC, but not in CT26 tumors. A FACS analysis also revealed that the majority of CD8 + T cells in CT26 tumors were specific to the retroviral AH1 antigen. Abstract : What's new? While pro‐inflammatory cytokines can potentially boost T‐cell activity within tumors, producing anticancer effects, cytokine products induce dose‐limiting side effects. This limitation may be overcome, however, by the fusion of cytokines with tumor‐targeting antibodies. Here, the authors investigated the immunotherapeutic effects of a novel fusion protein consisting of murine interleukin‐12 cytokine and L19 antibody (L19‐mIL12). In CT26 tumor‐bearing mice, L19‐mIL12 exerted significant antitumor activity, increasing NK and CD8+ cell concentrations in tumors and curing 60 percent of animals. L19‐mIL12 activity was potentiated by CTLA‐4 or PD‐1 blockade. The findings provide a basis for the clinical study of human L19‐mIL12 analogs.